2016
DOI: 10.1038/srep27867
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous photoluminescence in InP1−xBix

Abstract: Low temperature photoluminescence (PL) from InP1−xBix thin films with Bi concentrations in the 0–2.49% range reveals anomalous spectral features with strong and very broad (linewidth of 700 nm) PL signals compared to other bismide alloys. Multiple transitions are observed and their energy levels are found much smaller than the band-gap measured from absorption measurements. These transitions are related to deep levels confirmed by deep level transient spectroscopy, which effectively trap free holes and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…To act as a surfactant, there have to be enough Bi atoms impinged onto the matrix material [202]. If the Bi content is too high or the growth temperature is too low, Bi tends to segregate and even form droplets on the surface, deteriorating the material morphology.…”
Section: Surfactant Effect and Segregationmentioning
confidence: 99%
“…To act as a surfactant, there have to be enough Bi atoms impinged onto the matrix material [202]. If the Bi content is too high or the growth temperature is too low, Bi tends to segregate and even form droplets on the surface, deteriorating the material morphology.…”
Section: Surfactant Effect and Segregationmentioning
confidence: 99%
“…16,18 The native P In donor level was indicated to be about 0.2-0.3 eV below the conduction band, 17,31 and the acceptor level due to Bi pairs/clusters was found at about 0.11 eV above the valence band in InP 0.975 Bi 0.025 . 17 In addition, theoretical simulations suggested that the Bi In anti-site exists in InPBi and the energetic level is located at about 0.39 eV below the conduction band of InPBi at RT.…”
Section: Tmentioning
confidence: 97%
“…17 In addition, theoretical simulations suggested that the Bi In anti-site exists in InPBi and the energetic level is located at about 0.39 eV below the conduction band of InPBi at RT. 33 It therefore seems to be a hint that the A-and B-features may be attributed to the Bi Into-Bi pairs/clusters and P In -to-Bi pairs/clusters transitions, respectively; and C-and D-features the Bi In -and P In -levels to the Bi pairs/clusters-irrelevant shallow-acceptor levels transitions.…”
Section: Tmentioning
confidence: 99%
See 2 more Smart Citations